Optimizing a human monoclonal antibody for better neutralization of SARS-CoV-2 - Qian Wang; Yicheng Guo; Ryan G. Casner; Jian Yu; Manoj S. Nair; Jerren Ho; Eswar R. Reddem; Ian A. Mellis; Madeline Wu; Chih-Chen Tzang; Hsiang Hong; Yaoxing Huang; et al. (Nature Communications)
Abstract SARS-CoV-2 has largely evolved to resist antibody pressure, with each successive viral variant becoming more and more resistant to serum antibodies in the population. This evolution renders all previously authorized anti-spike therapeutic monoclonal antibodies inactive, and it threatens the remaining pipelines against COVID-19. We report herein the isolation of a human monoclonal antibody with a broad but incomplete SARS-CoV-2 neutralization profile, but structural analyses and mutational scanning lead to the engineering of variants that result in greater antibody flexibility while binding to the viral spike. Three such optimized monoclonal antibodies neutralize all SARS-CoV-2 strains tested with much improved potency and breadth, including against subvariants XEC and LP.8.1. The findings of this study not only present antibody candidates for clinical development against COVID-19, but also introduce an engineering approach to improve antibody activity via increasing conformational flexibility.